Nanoindentation characterization of shale micromechanics and fracturing ability evaluation of reservoir - Lichao CHEN; Diankun ZHANG; Yuhang XIAO; Shengwei WANG; Shuaifeng LYU (Meitan xuebao)
The micromechanical properties of shale are the key basis for shale reservoir compressibility evaluation. In this paper, the Marine shales of Longmaxi Formation in Sichuan Basin, Changhanguou Formation in Shiguai Basin in Inner Mongolia and Yangye Formation continental shales in Tarim Basin are selected as objects. The elastic mechanical properties, hardness, and fracture toughness parameters of shales are obtained by nano-indentation test. A method for evaluating shale brittleness is proposed. The fracture extension forms of reservoir fracturing are constructed. Finally, the evaluation index system of shale reservoir engineering mechanical quality is proposed. The results show that: The hysteretic loops of shale loading and unloading curves in Sichuan Basin, Shiguai Basin in Inner Mongolia and southwestern Tarim Basin increase, indicating that the proportion of plastic deformation energy of shale increases, indicating that rock brittleness is weakened. The test results show that the shale elastic modulus of Sichuan, Shiguai and Tarim basins are 60.27 GPa, 34.87 GPa and 23.40 GPa,the shale hardness of Sichuan, Shiguai and Tarim basins are 3.05 GPa, 1.21 GPa and 0.57 GPa, and the fracture toughness is 1.56, 0.75 and 0.28 MPa·m0.5, respectively. The stiffness and toughness of these shale rocks vary greatly. The fracture toughness of southern Sichuan shales is higher than that of Shiguai and southwest Tarim continental shales, which can form high net fracture pressure to form fracture turning and facilitate the construction of complex fracture network. However, the low fracture toughness of continental shale is not conducive to the pressure holding of fracture fluid, and it is difficult to reach the high net fracture fluid pressure, and the difficulty of fracture steering is not conducive to the formation of complex pressure fracture network. In this paper, the ratio of elastic energy, plastic energy and fracture energy during the indentation process (brittleness coefficient) is proposed to evaluate the brittleness of shale. The brittleness coefficient of Sichuan shale is 0.89, which belongs to elastic-brittleness shale, and the fractures under external load crack along mineral grain boundaries to form narrow cracks. The brittleness coefficient of crutchy shale is 0.27, which belongs to elastoplastic shale. The reservoir is highly heterogeneous, and the fractures form tortuous fractures when they encounter hard minerals. The brittleness coefficient of shale in Tarim Basin is 0.04, which is plastic shale and easy to form wide fractures. In this paper, a quantitative classification evaluation method for shale engineering mechanical quality is proposed based on seven indexes, including rock elastic modulus, hardness, fracture property, brittleness index, clay mineral content and mineral contact mode, in order to provide a quantitative scientific basis for shale reservoir fracturing quality evaluation and optimal selection of fracturing engineering desserts.